“Para se tratar da matéria dos quintos”: a dinâmica da arrecadação dos quintos reais em Minas Gerais (c. 1701 - c. 1780) - Simone Faria (Centre de Recherches sur les Mondes Américains, 2013)
The present text, result of current investigations for my doctoral thesis, focuses on attending to important aspects of the complex dynamics of the gold collection due to the Portuguese Crown in the eighteenth century by the explorations in Minas Gerais. Analysing about 400 fiscal books, dedicated to the local registration of such activity, I try to see the nuances of the process collection or when it was made by the municipality or when she had taken care by the Real Fazenda, or more, or when these two institutions share tasks and combine individuals. This is essentially an attention declared to the quotidian functioning of the collection, custody, accommodation, transport, and remitting of the gold fifth to Portugal, standing back the analyses more statistics about the gold production and about the amounts received for Portugal. In this way, the main objective is to give to the knowledge of the fifth collection process a renovated perspective, that assigns a character more local and also more social to the studies connected to this fiscal subject.